Network pharmacology and experimental verification reveal the mechanism of safranal against glioblastoma (GBM) - Yang, Xiaobing; Lu, Di; Sun, Yanfei; Wei, Tiandi; Man, Dulegeqi; Chen, Anbin; Luo, Tao; Zhao, Feihu; Liu, Xuemeng; Cheng, Bo; Wang, Xu; Zhao, Peng; et al. (Frontiers in Oncology, 2023)
Safranal is an active component of the traditional Tibetan medicine (TTM) saffron, which has potential anticancer activity. Here, we studied the therapeutic effect and mechanism of safranal on GBM. CCK-8, GBM-brain organoid coculture experiments and 3D tumour spheroid invasion assays showed that safranal inhibited GBM cell proliferation and invasion in vitro. Network pharmacology, RNA-seq, molecular docking analysis，western blotting, apoptosis, and cell cycle assays predicted and verified that safranal could promote GBM cell apoptosis and G2/M phase arrest and inhibit the PI3K/AKT/mTOR axis. In vivo experiments showed that safranal could inhibit GBM cell growth alone and in combination with TMZ. This assay revealed that safranal inhibits GBM cell growth in vivo and in vitro, promotes GBM cell apoptosis and G2/M phase arrest, inhibits the PI3K/AKT/mTOR axis and cooperate with TMZ.